If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 33 = 5x + 87 Reorder the terms: 33 + 8x = 5x + 87 Reorder the terms: 33 + 8x = 87 + 5x Solving 33 + 8x = 87 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 33 + 8x + -5x = 87 + 5x + -5x Combine like terms: 8x + -5x = 3x 33 + 3x = 87 + 5x + -5x Combine like terms: 5x + -5x = 0 33 + 3x = 87 + 0 33 + 3x = 87 Add '-33' to each side of the equation. 33 + -33 + 3x = 87 + -33 Combine like terms: 33 + -33 = 0 0 + 3x = 87 + -33 3x = 87 + -33 Combine like terms: 87 + -33 = 54 3x = 54 Divide each side by '3'. x = 18 Simplifying x = 18
| 60y^2-51y-72=0 | | 3x^2-9x=30 | | d-(-4)=25 | | (2x+7)(x-8)=0 | | 3x^2+17x-12=0 | | 9g-6=3(4g+5) | | 3x^2-1/27x^6=0 | | 50=x+2y | | 8(x-1)-8=3x+5(-4+x) | | 15g^2-19gh-56h^2=0 | | -(-8n+2)=-4(-6+5n)+7n | | 2x^2-24=-8x | | z-8/z^2-8z | | 14+4=38 | | 8t+61=5 | | -(q+1)=-(4+q)+7q | | 29=-8t | | 7x-14=5x-2 | | 15=12m-9 | | 8g^2+6g-9=0 | | -5p-2(2p-6)=-5p+3 | | 11=9 | | 4x-5=9x+20 | | 4-4x=20x-5 | | y/5=65 | | 9=-(2-5t)-10t | | 3/16=p/40 | | 5(2)-12/3x2(2)=171/3 | | 3(6x-1)=29 | | -45-4x=90-10x | | 25-12/3(4)=171/3 | | x-x^4=0 |